PWE-046 The development of human esophageal pain hypersensitivity is associated with anxiety and sympathetic nervous system activation. (28th May 2012) - Botha, C A; Knowels, C H; Aziz, Q
Abstract : Introduction: Experimental acid infusion in the distal oesophagus leads to secondary hyperalgesia in the proximal oesophagus in most healthy subjects but 30% remain resistant. The factors that mediate differences in sensitisation to acid are unclear and their study may help to understand risk factors for esophageal hypersensitivity in gastro-esophageal reflux disease. We aimed to determine the psycho-physiological factors which predict the development of esophageal pain hypersensitivity (EPH) to acid infusion in healthy subjects. Methods: 52 healthy volunteers (mean age 29 yrs, range 19–49 yrs; 33 male) underwent psychological profiling for, anxiety, depression and personality type. Baseline pain thresholds (PT) to proximal esophageal electrical stimulation were measured before hydrochloric acid infusion (0.15 M) in the distal oesophagus for 30 min. This was followed by esophageal pain threshold measurements using visual analogue scales to electrical stimulation in the proximal, unexposed oesophagus at 30, 60 and 90 min. Parasympathetic (Cardiac Vagal Tone—CVT) and Sympathetic Nervous System (RR interval) responses were monitored throughout the study. Volunteers were classified as sensitisers if the proximal PT fell ≥6 mA after esophageal acidification. Results: Four subjects dropped out, 35 subjects (73%) sensitised to acid, and 13 subjects (27%) did not sensitise. There was no difference in the age, sex or in personality domains between sensitisers and non-sensitisers (p>0.05). Spielberg trait anxiety comparison indicated a trend, p=0.08 for sensitisers to be more anxious than non-sensitisers. At baseline there was no difference in CVT and RR interval between the two groups. During acid infusion the key difference in autonomic nerves system response was that in the sensitisers the RR interval was shorter in sensitisers than non-sensitisers (sensitisers: Δ1.7 SE±48.9 vs non-sensitisers: Δ66.1 SE±25.65. ΔRR interval difference 64.4 ms (SE ±37.3) p=0.002). Trait anxiety demonstrated a negative correlation with the RR interval r=−0.35 (p=0.04). Conclusion: There was a trend for sensitisers to be more anxious and at baseline there were no differences in the PNS and SNS parameters between the two groups. During acid infusion, the sensitisers had a lower RR interval than non-sensitisers suggesting a higher heart rate and therefore SNS tone. Trait anxiety showed a negative correlation with the RR interval suggesting those with higher anxiety had higher heart rate. Our results suggest that higher anxiety and SNS activation has a pro nociceptive effect on the development of post-acid infusion esophageal sensitisation. This may explain why individuals with anxiety or stress at the time of visceral injury or inflammation are more likely to go onto develop EPH. Competing interests: None declared.